2012
DOI: 10.1136/bjsports-2012-091204
|View full text |Cite
|
Sign up to set email alerts
|

Hip pads reduce the overall risk of injuries in recreational snowboarders

Abstract: The use of hip pads is recommended for snowboarders as it reduces the overall risk of common snowboarding injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Table 2 depicts general demographics and emergency characteristics. Men were older than women (24 (16-34) vs 21 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31); p<0.001) and more frequently involved in accidents while actively on a downhill run (83.9% vs 78.4%; p<0.001), while snowboarding in a park (4.8% vs 2.1%; p<0.001) and alcoholised (1.6% vs 0.5%; p<0.001). Accidents while snowboarding on a slope were most frequent in both genders, but men were more frequently affected on slopes with higher difficulty levels (red: 42.6% vs 39.9%; p=0.037; black: 4.2% vs 2.5%; p=0.003).…”
Section: Emergency and Injury Characteristicsmentioning
confidence: 99%
“…Table 2 depicts general demographics and emergency characteristics. Men were older than women (24 (16-34) vs 21 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31); p<0.001) and more frequently involved in accidents while actively on a downhill run (83.9% vs 78.4%; p<0.001), while snowboarding in a park (4.8% vs 2.1%; p<0.001) and alcoholised (1.6% vs 0.5%; p<0.001). Accidents while snowboarding on a slope were most frequent in both genders, but men were more frequently affected on slopes with higher difficulty levels (red: 42.6% vs 39.9%; p=0.037; black: 4.2% vs 2.5%; p=0.003).…”
Section: Emergency and Injury Characteristicsmentioning
confidence: 99%
“…Injury statistics have shown that skiing injuries mainly involve the lower extremities, predominantly the knee (18.1%–36.7%) [ 4 8 ] and the ankle joint (6%–12.2%) [ 6 , 9 – 11 ]. In snowboarding, injuries occur when falling or during landings after a jump and mainly the upper extremities are injured [ 7 , 8 , 12 ]. However, still a considerable number of injuries occur in the lower extremities, with 6.4–17% in the knee joint and 4.9%–16% in the ankle joint [ 7 , 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 The most common snowboarding injuries are distal radial fracture (Figure 1), followed by closed head injury and acromioclavicular fracture (Figure 2). 4 A high proportion of snowboarders who are injured are beginners. Novices are at increased risk of wrist injuries particularly due to frequent falls.…”
Section: Types Of Injuriesmentioning
confidence: 99%
“…The use of hip pads is recommended for snowboarders as it reduces the overall risk of common snowboarding injuries. 4 Mountain safety precautions such as widening of runs and streamlining of high traffic areas, training medical providers to recognize and treat sport-specific injuries, and promoting the use of wrist guards and helmets may be useful in reducing the effect that snowboarders have on ski resort injuries. 2…”
Section: Preventing Strategiesmentioning
confidence: 99%